A description of the elevation of pericardial cortisol: cortisone ratio in patients with tuberculous pericarditis - Shenje, Justin Tapiwa; Raubenheimer, Peter; Wiesner, Lubbe; Ross, Ian (Frontiers in Endocrinology, 2023)
Pulmonary Tuberculosis is an inflammatory disease associated with an elevated cortisol/ cortisone ratio at the site of infection and an array of cytokine changes. Tuberculous pericarditis is a less common, but more lethal form of tuberculosis and has a similar inflammatory process in the pericardium. As the pericardium is largely inaccessible, the effect of tuberculous pericarditis on pericardial glucocorticoids is largely unknown. We wished to describe pericardial cortisol/ cortisone ratio in relation to plasma and saliva cortisol/ cortisone ratios and the associated changes in cytokine concentrations. The median (interquartile range) of plasma, pericardial and saliva cortisol concentration was; 443 (379-532) nmol/l, 303 (257-384) nmol/l and 20 (10-32) nmol/l, respectively, while the median (interquartile range) of plasma, pericardial and saliva cortisone concentrations were; 49 (35-57) nmol/l, 15.0 (0.0-21.7) nmol/l and 37 (25-55) nmol/l, respectively. The cortisol/ cortisone ratio was highest in pericardium with median (interquartile range) 20 (13 – 445), followed by plasma 9.1 (7.4 – 12.1), and saliva 0.4 (0.3 – 0.8). The elevated cortisol/ cortisone ratio was associated with elevated pericardial, interferon gamma, tumour necrosis factor alpha, interleukin 6, interleukin 8 and induced protein 10. Administration of a single dose of 120 mg of prednisolone was associated with suppression of pericardial cortisol and cortisone within 24 hours of administration. The cortisol/ cortisone ratio was highest at the site of infection, in this case the pericardium. The elevated ratio was associated with a differential cytokine response. The observed pericardial cortisol suppression suggests that 120 mg of prednisolone was sufficient to evoke an immunomodulatory effect in the pericardium.